An experimental approach to evaluate the stability and thermal conductivity of SiO₂/oil as green nanolubricant - Anwar Ilmar Ramadhan; Tri Yuni Hendrawati; Kushendarsyah Saptaji; Efrizon Umar; Kukuh Haryadi (Mechanical Engineering for Society and Industry, 2026)
The application of nanotechnology in lubrication science has enabled the creation of nanolubricants with superior stability, improved thermal performance, and greater environmental compatibility than conventional lubricants. In this work, the stability and thermal conductivity of SiO₂ nanoparticles dispersed in base oil were experimentally examined as a green nanolubricant. SiO₂ nanoparticles were chosen owing to their chemical inertness, excellent thermal resistance, and eco-friendly nature. The nanolubricants were synthesized using a two-step method at volume concentrations of 0.1%, 0.2%, and 0.3%, with ultrasonication applied to ensure uniform particle distribution. Their stability was assessed using UV–Vis spectrophotometry, zeta potential testing, and visual sedimentation monitoring over 30 days. Thermal conductivity was determined via the transient hot-wire method. The results demonstrated that incorporating SiO₂ nanoparticles enhanced thermal conductivity by up to 12% compared to the base lubricant. Furthermore, stability evaluation showed zeta potential values of 41.2 mV, confirming strong electrostatic repulsion and low levels of agglomeration. Overall, these outcomes emphasize the promise of SiO₂-based green nanolubricants for thermal engineering applications, offering efficient and sustainable substitutes for traditional lubricants.